Gender and geographic differences in Medicare service utilization during the last six months of life. (2nd November 2018) - Crouch, Elizabeth; Probst, Janice; Bennett, Kevin; Eberth, Jan
ABSTRACT: End-of-life issues are important for senior women, particularly rural women, who are more likely than their urban counterparts to live alone. The role of residence as a factor for health-care utilization among Medicare beneficiaries during the last six months of life has yet to be investigated. The purpose of this study is to examine whether service utilization in the last six months of life differs across gender and rurality. The sample was restricted to fee-for-service Medicare beneficiaries who died between July 1, 2013, and December 31, 2013 ( n  = 39, 508). The odds of rural beneficiaries using home health (aOR 0.87; 95% CI 0.81–0.93) and/or hospice (aOR 0.82; 95% CI 0.77–0.87) in the last six months of life were lower than urban beneficiaries. Female beneficiaries were more likely to use support services such as hospice (aOR 1.24; 95% CI 1.18–1.29) and/or home health services (aOR 1.07; 95% CI 1.02–1.13) than male beneficiaries. The odds of female beneficiaries using inpatient (aOR 1.14; 95% CI 1.08–1.20) and/or outpatient (aOR 1.06; 95% CI 1.01–1.12) were higher than male beneficiaries. This research is important as we examine the range of health services used during the last six months of life, by gender and rurality. Future research is needed to understand how access to health services, residential isolation, and age- and disease-related factors relate to women's observed greater use of inpatient, outpatient, hospice, and home health services in the last six months of life.